Pengembangan Media Animasi Interaktif Berbantuan Levideo Pada Pelajaran IPS Kelas IV Sekolah Dasar - Denis Santoso; Diana Pramesti; Romadon Romadon (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This study aims to produce a product in the form of Levideo Assisted Interactive Animation Media to overcome problems in social studies learning in elementary schools. This research used the R&D (Research and Development) development method. The results were obtained from the material validator with a percentage value of 90% (very feasible), 88% media validator (very feasible), and language validator with 80% (adequate). The practicality of the media was obtained from the students' responses to the small-scale test, and the large- scale test obtained 95% and 94% (very practical), the practicality of the media from the teacher was obtained 94% (very practical). The study results showed that the media developed is very feasible and practical to use as a learning medium, especially in social studies learning material about the beauty of my country's cultural diversity.